Upaya Meningkatkan Kemajuan UMKM Kemplang Asrania di Pemulutan Ilir Melalui Peningkatan Kualitas SDM - Helmi, Sulaiman; Rosa, Alkirma; Ariana, Sunda (MBIA, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the Indonesian economy but still require development, especially in improving the quality of human resources. Focusing on improving human resources in MSMEs, such as those of Ms. Asrania's Kemplang Business in Pemulutan Ilir, is crucial to improving the competitiveness and sustainability of MSMEs. The study aimed to investigate ways to enhance the advancement of Kemplang MSMEs by enhancing the caliber of their workforce. This endeavor seeks to offer deeper insights and a significant contribution to the field of science, particularly in the micro, small, and medium-sized economies, laying a foundation for future research in this domain. The MSME development program through improving human resources in Pemulutan Ilir Village lasted for two months and targeted the community around the village. "The techniques applied were participatory and action research, which involved the participation of students and villagers to address specific problems faced by MSMEs and play a role in advancing the local economy. Kemplang Asrania MSMEs improve employee skills through hands-on training, on-the-job methods, demonstrations, and examples. They also apply Coaching and Counseling as a short-term educational approach while still taking into account work experience when hiring the team. Training, coaching, and counseling have positively impacted the business's sustainability and development while paying attention to Sharia's values in improving the quality of human resources. Keywords: MSMEs, Human Resources, Quality Improvement Abstrak Usaha Mikro Kecil Menengah (UMKM) memegang peranan penting dalam ekonomi Indonesia, tetapi masih memerlukan pengembangan terutama dalam meningkatkan kualitas SDM. Fokus pada peningkatan SDM di UMKM, seperti yang dilakukan oleh Usaha Kemplang Ibu Asrania di Pemulutan Ilir, menjadi krusial untuk meningkatkan daya saing dan keberlanjutan UMKM. Penelitian dilaksanakan dengan maksud untuk mengeksplorasi upaya meningkatkan kemjuan UMKM Kemplang melalui peningkatan kualitas SDM, diharapkan memberikan pemahaman yang lebih baik dan kontribusi penting dalam pengembangan ilmu pengetahuan terutama dalam konteks ekonomi mikro, kecil, dan menengah serta menjadi dasar bagi penelitian lanjutan di bidang ini. Program pengembangan UMKM melalui peningkatan SDM di Desa Pemulutan Ilir yang berlangsung selama 2 bulan dengan sasaran masyarakat sekitar desa. Teknik yang diterapkan adalah partisipatif dan penelitian aksi, yang melibatkan partisipasi penduduk desa untuk menangani masalah spesifik yang dihadapi UMKM, serta berperan dalam memajukan perekonomian lokal. UMKM Kemplang Asrania meningkatkan keterampilan karyawan melalui pelatihan langsung, metode On the Job, serta demonstrasi dan example. Mereka juga menerapkan Coaching dan Counseling sebagai pendekatan pendidikan jangka pendek, sambil tetap memperhitungkan pengalaman kerja saat merekrut tim. Training, Couching dan Counseling ini telah berdampak positif bagi keberlangsungan dan perkembangan usaha, sambil memperhatikan nilai-nilai syariah dalam peningkatan kualitas SDM. Kata kunci: UMKM, SDM, Peningkatan Kualitas